Impact of Social Deprivation on Hospitalization and Intensive Care Unit Admission among COVID-19 Patients: A Systematic Review and Meta-Analysis - Yang-Jie Zhu; Kang Tang; Fang-Jie Zhao; Bo-Yang Yu; Tong-Tong Liu; Lu-Lu Zhang (Iranian Journal of Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected socially disadvantaged groups; however, the association between socioeconomic status and healthcare utilization among COVID-19 patients remains unclear. Therefore, a systematic review and meta-analysis was conducted to assess the association between socioeconomic status and hospitalization and intensive care unit admission among COVID-19 patients.